2020
DOI: 10.1093/nsr/nwaa263
|View full text |Cite
|
Sign up to set email alerts
|

Herpetological phylogeographic analyses support a Miocene focal point of Himalayan uplift and biological diversification

Abstract: The Himalaya are among the youngest and highest mountains in the world, but the exact timing of their uplift and origins of their biodiversity are still in debate. The Himalayan region is a relatively small area but with exceptional diversity and endemism. One common hypothesis to explain the rich montane diversity is uplift-driven diversification–that orogeny creates conditions favoring rapid in situ speciation of resident lineages. We test this hypothesis in the Himalayan region using amphibians and reptiles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 37 publications
8
43
0
Order By: Relevance
“…Time-tree analysis shows that most Angolan Hemidactylus lineages have diversified during the Miocene, coinciding with a progressively cooling climate and increased climatic seasonality in southern Africa, leading to the expansion of moist savannas and increased ecological heterogeneity (Herbert et al 2016), which has been associated with speciation across different taxonomical groups, including reptiles (Gamble et al 2008;Agarwal and Karanth 2015;Zimkus et al 2017;Werneck et al 2018;Xu et al 2020). The currently recognized Angolan Hemidactylus (with the exception of H. mabouia which is a widespread species across Africa and the Americas) could be traced to seven recognized lineages at the end of the Miocene.…”
Section: Discussionmentioning
confidence: 99%
“…Time-tree analysis shows that most Angolan Hemidactylus lineages have diversified during the Miocene, coinciding with a progressively cooling climate and increased climatic seasonality in southern Africa, leading to the expansion of moist savannas and increased ecological heterogeneity (Herbert et al 2016), which has been associated with speciation across different taxonomical groups, including reptiles (Gamble et al 2008;Agarwal and Karanth 2015;Zimkus et al 2017;Werneck et al 2018;Xu et al 2020). The currently recognized Angolan Hemidactylus (with the exception of H. mabouia which is a widespread species across Africa and the Americas) could be traced to seven recognized lineages at the end of the Miocene.…”
Section: Discussionmentioning
confidence: 99%
“…The Himalayas experienced upheaval for another 3000 m in the Pleistocene around 3–2.5 and 0.98 Ma due to renewed and considerable tectonic activity (Spicer et al, 2003; Spicer, 2017; Manish & Pandit, 2018). This stepwise uplift model for the Himalayas with the initial start from the Paleocene but with further extensive uplifting until the Miocene was also parallel to the animal diversification in this region (Xu et al, 2021). However, some authors suggested that the Himalayas, shared the same block and upheavals with the plateau platform during several major periods (Harrison et al, 1992; Molnar et al, 1993; Manish & Pandit, 2018).…”
Section: The Debates Between the Origin Of Species Diversity And Qtp “Uplift”mentioning
confidence: 93%
“…The accelerated diversification and colonization of these alpine lineages since the middle Oligocene were likely driven jointly by orogeny (mountain uplift) events and monsoon intensification. Similarly, Xu et al (2021) dated the origins of the Himalayan herpetofauna (using phylogenies of multiple groups) back to the early Paleocene although the rapid diversification of most lineages occurred in the Miocene.…”
Section: Species Diversification In the Qtpslmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent large-scale studies of species diversification on the QTP have provided convincing evidence for a Miocene diversification in plant lineages (Ding et al ., 2020) as well as amphibians and reptiles (Xu et al ., 2020). A hypothesis for the rich biodiversity found in mountainous regions like the QTP is uplift-driven diversification—that orogenic activities create diverse habitats favoring rapid in situ speciation of resident lineages (Xing & Ree, 2017; Chen et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%